Scaling and Disordered Systems 2002
DOI: 10.1142/9789812778109_0028
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in Cosmic Structures

Abstract: The study of the properties of cosmic structures in the universe is one of the most fascinating subject of the modern cosmology research. Far from being predicted, the large scale structure of the matter distribution is a very recent discovery, which continuosly exhibits new features and issues. We have faced such topic along two directions; from one side we have studied the correlation properties of the cosmic structures, that we have found substantially different from the commonly accepted ones. ¿From the ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…The fractal proponents (Pietronero et al 1997) have estimated D 2 ≈ 2 for all scales up to ∼ 500 h −1 Mpc, whereas other groups have obtained scale-dependent values (for review see Wu et al 1999 and references therein).…”
Section: Is the Universe Fractal ?mentioning
confidence: 99%
“…The fractal proponents (Pietronero et al 1997) have estimated D 2 ≈ 2 for all scales up to ∼ 500 h −1 Mpc, whereas other groups have obtained scale-dependent values (for review see Wu et al 1999 and references therein).…”
Section: Is the Universe Fractal ?mentioning
confidence: 99%
“…While Ribeiro (1992b) showed that an unperturbed EdS model does not have scale invariant features, in the sense of not having a power law decay of the average density at increasing depths, it, nevertheless, also showed very clearly that there is indeed a strong decay of the average density at increasing values of the luminosity distance or the redshift, an effect termed by Ribeiro (1995) as "observational inhomogeneity of the standard model". 2 Bearing this result in mind, it is only natural to ask whether or not a perturbed model could turn the density decay at increasing redshift depths into a power law type decay, as predicted, and claimed to be observed, by the scale invariant description of galaxy clustering (Pietronero 1987;Coleman and Pietronero 1992;Pietronero et al 1997;Ribeiro and Miguelote 1998;Sylos-Labini et al 1998;Pietronero and Sylos-Labini 2000).…”
Section: Introductionmentioning
confidence: 96%
“…It can be shown [25] that the mass function of a multifractal in a well defined volume, has a Press-Schechter shape with the exponent δ that depends on the shape of f (α). Moreover the fractal dimension of the support is D(0) = f (α s ) = 3 − γ (eq.…”
Section: The Multifractal Mass Distributionmentioning
confidence: 99%
“…The evidence that galaxian luminosity and location in space are not independent and that, on the contrary, are strongly correlated have important consequences in all the luminosity properties of visible matter and in relation to the methods that are usually used to study these properties [11], [25].…”
Section: The Multifractal Mass Distributionmentioning
confidence: 99%